HIV-1 CRF_BC Recombinants Infection in China: Molecular Epidemic and Characterizations - Ouyang, Yabo; Shao, Yiming; Ma, Liying (Current HIV Research, 2012)
CRF_BC recombinant strains were first identified in China and are one of the most prevalent and characteristically unique HIV-1 subtypes across China. Here we aim to review the published data about HIV-1 CRF_BC recombinant strains epidemic in China and to characterize the genetics, biology and drug resistance of this virus. This study may help to better understand the current situation of HIV-1 CRF_BC prevalence and facilitate the development of vaccines and more efficient anti-HIV-1 regimens in China.
Keywords: HIV-1